Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ani9090662
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Welfare of Companion Dogs—Is Owner Education the Solution?

Abstract: Simple SummaryThe welfare of most dogs living in homes is largely unknown. However, national surveys carried out by animal welfare charities and findings by animal welfare researchers have shown significant deterioration in some key aspects of dog welfare. For example, more dogs presenting to vets with behavioural problems, obesity, and ill-health due to poor breeding practices. This means that some dogs are suffering due to their owners’ behaviours or ownership practices. Educating dog owners as to how best t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 95 publications
2
36
0
1
Order By: Relevance
“…Conclusive results were obtained regarding the feeling generated from their interactions with their pet(s) and the benefits they provided to the participants’ well-being from a biopsychosocial perspective, which is in line with previous research [ 58 , 84 ]. Additionally, the applied models showed that living with an animal provided important benefits for the humans, in agreement with the evidence found in recent research [ 28 , 85 , 86 , 87 ].…”
Section: Discussionsupporting
confidence: 90%
“…Conclusive results were obtained regarding the feeling generated from their interactions with their pet(s) and the benefits they provided to the participants’ well-being from a biopsychosocial perspective, which is in line with previous research [ 58 , 84 ]. Additionally, the applied models showed that living with an animal provided important benefits for the humans, in agreement with the evidence found in recent research [ 28 , 85 , 86 , 87 ].…”
Section: Discussionsupporting
confidence: 90%
“…Although the owner-dog relationship is influenced by both canine and human characteristics [16], research suggests that the owner plays a very important part in the affective state and subsequent behavior of the dog [17]. The behaviors of owners toward their dogs are influenced by multiple factors [18], such as the owner's attitudes and beliefs about dogs, previous experiences with dogs, perceptions of society and peers, and biased views on personal knowledge and skills, as well as self-efficacy, which may change over time. Understanding people's attitudes and behaviors towards animals is challenging and complex but of great importance if we seek to prevent problems.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the deficit model overlooks the underlying beliefs, existing attitudes and motivations for current practices. We now recognize that the deficit model is not the most effective way to communicate, engage stakeholders and effect change (22,23).…”
Section: Communicationmentioning
confidence: 99%